2021
DOI: 10.1186/s12903-021-02025-w
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cranberry juice and a cranberry functional beverage on the growth and metabolic activity of selected oral bacteria

Abstract: Background The oral microbiota is a significant risk indicator for oral diseases, such as dental caries and periodontal inflammation. Much attention is presently paid to the development of functional foods (e.g. beverages containing cranberry constituents, or foods containing probiotics) that may serve as adjuncts for oral disease treatments (e.g. periodontitis and caries). Cranberry fruit, due to its unique chemical composition and antimicrobial potential, is a possible ingredient of such food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 80 publications
0
18
0
Order By: Relevance
“…As illustrated in Figure 2a, peak I intensities were higher in the XRD pattern of the A-DDC group, suggesting that aloin may induce a shorter lateral spacing between collagen molecules (Green et al, 2017). This conjecture is further supported by the observed increase in 2θ angles of the diffraction peak I and III in the A-DDC group, indicating that the addition of aloin reduces the spacing between collagen molecules (Ding et al, 2019;Nwambaekwe et al, 2021). Peak II, which can be seen at roughly 2θ ~20°, is due to the diffusive scattering caused by the presence of random-coil structures embedded within the collagen fibers (Giraud-Guille et al, 2000).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…As illustrated in Figure 2a, peak I intensities were higher in the XRD pattern of the A-DDC group, suggesting that aloin may induce a shorter lateral spacing between collagen molecules (Green et al, 2017). This conjecture is further supported by the observed increase in 2θ angles of the diffraction peak I and III in the A-DDC group, indicating that the addition of aloin reduces the spacing between collagen molecules (Ding et al, 2019;Nwambaekwe et al, 2021). Peak II, which can be seen at roughly 2θ ~20°, is due to the diffusive scattering caused by the presence of random-coil structures embedded within the collagen fibers (Giraud-Guille et al, 2000).…”
Section: Discussionmentioning
confidence: 55%
“…In the presence of bacteria and enzymes, as well as changes in temperature, apatite mineral crystals in the enamel and dentin gradually deteriorate, exposing the underlying organic dental collagen network (Wang, Wang, et al., 2022 ). When dental collagen is exposed, it becomes more vulnerable to external infections, and its triple‐helix structure deteriorates rapidly (Nowaczyk et al., 2021 ). Loosening of the collagen structure and the high porosity of the collagen network facilitate the diffusion of infectious substances.…”
Section: Introductionmentioning
confidence: 99%
“…Bias evaluation was performed according to the parameters established in Table 2 . The main risk of bias was found in that study limitations were either not reported in the study report [ 24 26 , 29 , 36 , 37 , 39 , 41 43 ] or were described briefly [ 27 , 28 , 31 34 , 40 , 44 ]. Secondly, there was a failure to include relevant ethical aspects such as institutional ethics committee approval, or patient informed consent for saliva sample collection was not clearly detailed in the article text, or a declaration of project financing and conflict of interest was absent [ 27 – 29 , 31 37 , 39 42 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…NDM can inhibit the proliferation of P.gingivalis , T.forsythia , and T.denticola in periodontal pockets. Unusual production of cytokines by host cells caused by periodontopathogens damage tooth-supporting tissues; studies have demonstrated that cranberry was an excellent inhibitor of pro-inflammatory cytokine and chemokine replies caused by lipopolysaccharides [ 124 , 133 , 134 ].…”
Section: Cranberry ( V Sect Oxycoccus ...mentioning
confidence: 99%